Superior hydrophobic silica-coated quantum dot for stable optical performance in humid environments. (7th May 2022) - Zhou, Shuling; Xie, Bin; Yang, Xuan; Zhang, Xinfeng; Luo, Xiaobing
Abstract: Quantum dot (QD) features many exceptional optical performances but is also vulnerable to moisture which results in structural damage and luminescent decrease. This work provided and fabricated a novel superior hydrophobic methylated core/shell silica-coated QD (MSQ) for high water stability. QD was coated with a silica shell and then surface-methylated by trimethyl silane. Mercaptopropyl trimethoxy silane, tetraethyl orthosilicate, and ethoxy trimethyl silane were utilized as the ligand exchanger, the raw material of silica, and the surface modification, respectively. Characterization results illustrated the core/shell structure of MSQ. In addition, its water contact angle was up to 159.6°. QD-, silica-coated QD(SQ)-, and MSQ-silicone were made and displayed similar absorption, emission, and excitation spectra but different water stabilities. The photoluminescence intensity and photoluminescence quantum yield of MSQ-silicone hardly changed during 15 d of water immersion, in contrast to the dramatical decrease of other two kinds of composite silicone. Specifically, the photoluminescence quantum yield decreases of MSQ-, SQ-, and QD-silicone were 1%, 40%, and 43%, respectively. Therefore, MSQ had a much better water stability. The superior hydrophobic methylated silica-coated QD has a great potential to realize the long-term working stability in a humid environment and the wider application in diverse fields.